Assessing strength asymmetries with rotational inertial technology: exercise-specific patterns and temporal changes in professional male soccer players - Murillo-Ortiz, A.; Raya-Gonzalez, J.; Falces-Prieto, M.; Lopez-Mariscal, S.; Iglesias-Garcia, F. J.; Martinez-Aranda, L. M. (Sports, 2026)
Inter-limb asymmetries are common in soccer players and are frequently monitored in high-performance settings; however, their expression across different flywheel-based strength exercises, movement phases, and over time remains unclear. This study aimed to (i) compare inter-limb power asymmetry magnitudes across multiple unilateral flywheel exercises and between concentric (CON) and eccentric (ECC) phases, and (ii) describe changes in these asymmetries over an 8-week period of routine soccer training, stratified by baseline asymmetry magnitude. The present study was designed as an observational and descriptive study. Twenty-one professional male soccer players completed two testing sessions separated by eight weeks. Players performed six unilateral flywheel exercises targeting hip- and knee-dominant quadriceps (Qhip, Qknee), hip- and knee-dominant hamstrings (Hhip, Hknee), adductors (ADD), and abductors (ABD). For each exercise and limb, the repetition with the highest CON mean power and its consecutive ECC phase were selected for analysis. Inter-limb asymmetry (%) was calculated for mean and peak power in both phases. Across exercises, ECC asymmetries were generally greater than CON asymmetries, with the largest values observed for Qknee peak power (CON: 12.86 ± 11.04%; ECC: 27.60 ± 13.65%) and Hknee peak power (CON: 10.45 ± 11.26%; ECC: 24.01 ± 20.46%). Exercise-specific patterns were evident, with generally weak associations between asymmetries across tasks. Over time, players classified with higher baseline asymmetry (>=10%) presented lower values at follow-up in several outcomes (particularly ECC-related measures), whereas players with lower baseline asymmetry (<10%) showed small increases or remained stable; These between-group patterns should be interpreted cautiously, as they may be more strongly influenced by regression to the mean and measurement variability than by underlying physiological changes. Overall, inter-limb power asymmetries assessed with flywheel technology were phase- and exercise-specific in this professional soccer sample. These descriptive findings may help contextualize phase-specific and multi-exercise asymmetry monitoring in professional soccer settings.